Development of mechanically-robust piezoelectric micromachined ultrasonic transducer based on island-shaped monocrystalline PZT thin film partially covered with polyimide. (11th November 2020) - Thao, Pham Ngoc; Yoshida, Shinya; Tanaka, Shuji
Abstract: This paper describes a new design of piezoelectric micromachined ultrasonic transducer (pMUT) with a monocrystalline Pb(Zr, Ti)O3 -based thin film (Mono-PZT) for enhancing the mechanical robustness. In this study, we investigated two design concepts to suppress crack generation in Mono-PZT. First, the area of Mono-PZT is limited by leaving an island Mono-PZT pattern only on the membrane of the pMUT. Second, the edge of Mono-PZT is covered with a polyimide (PI) thin film as a protection layer to prevent the peeling. We prepared three different designs, a new design with both concepts, another design with the first concept, and the conventional one with neither of them for comparison. The robust mechanical analyses of these devices were performed by driving resonantly and increasing the displacement of the membranes. As these results, the proposed structure with both concepts still stands well at the highest displacement, 1600 nm, while the undesired cracks occur on other structures with approximately 800 nm of displacement. The robustness could improve 50% in comparison to the other designs thanks to this unique design. Finite element method simulation results showed that this PI layer contributed to decrease the stress concentrated at the edge both in the static condition and in the dyanamic vibarion of the membrane. This layer also probably played a role in prevention of the peeling of the edge of the island-shaped Mono-PZT. In conclusion, the new design is useful for the Mono-PZT pMUT in terms of excellent mechanical robustness.